IS26-mediated cointegration generates a plasmid co-harbouring blaIMP-4 and blaKPC-2 in Klebsiella pneumoniae - Jiawei Zhou (Journal of Global Antimicrobial Resistance, 2025)
Background: This study aims to explore the phenotypic and genotypic characteristics of a plasmid that co-harbours blaIMP-4 and blaKPC-2 in a carbapenem-resistant Klebsiella pneumoniae. Methods: Strain K194 was isolated from a 60-year-old patient. Species identification was performed with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, followed by antibiotic susceptibility testing. Antimicrobial resistance genes were detected and S1-pulsed-field gel electrophoresis with Southern blot experiments were performed to identify plasmids. Whole-genome sequencing was executed with the Illumina and Oxford Nanopore platforms. Results: K. pneumoniae K194 was resistant to multiple antibiotics, including carbapenems. This strain carried both blaIMP-4 and blaKPC-2 on a single 163 kb plasmid (pK194-P2). pK194-P2 was capable of conjugation with an efficiency of 3.4 × 10–7 in vitro conjugation experiments. Whole-genome analysis confirmed that pK194-P2 was a novel plasmid and had both IncFII- and IncN-type replicons. Sequence alignment revealed direct repeats of the sequences (GCCCAAGG) flanking a 109-kb region bounded by two copies of IS26. In vitro, evolution experiments showed that blaKPC-2 in pK194-P2 could be stably maintained in the transconjugants after 10 days of passage, while blaIMP-4 could be lost during repeated laboratory passage. Whole-genome sequencing and alignment of two blaIMP-4-negative plasmids with pK194-P2 revealed that they had a deletion of 81 or 94 kb adjacent to IS26. Conclusions: Our study reports a novel plasmid co-harbouring blaIMP-4 and blaKPC-2 in K. pneumoniae, and highlights the potential role of IS26-mediated cointegration and deletion in plasmid formation and evolution.